LPS-Induced Acute Kidney Injury Is Mediated by Nox4-SH3YL1 - Jung-Yeon Yoo; Dae Ryong Cha; Borim Kim; Eun Jung An; Sae Rom Lee; Jin Joo Cha; Young Sun Kang; Jung Yeon Ghee; Jee Young Han; Yun Soo Bae (Cell Reports, 2020)
Summary: Cytosolic proteins are required for regulation of NADPH (nicotinamide adenine dinucleotide phosphate) oxidase (Nox) isozymes. Here we show that Src homology 3 (SH3) domain-containing YSC84-like 1 (SH3YL1), as a Nox4 cytosolic regulator, mediates lipopolysaccharide (LPS)-induced H2O2 generation, leading to acute kidney injury. The SH3YL1, Ysc84p/Lsb4p, Lsb3p, and plant FYVE proteins (SYLF) region and SH3 domain of SH3YL1 contribute to formation of a complex with Nox4-p22phox. Interaction of p22phox with SH3YL1 is triggered by LPS, and the complex induces H2O2 generation and pro-inflammatory cytokine expression in mouse tubular epithelial cells. After LPS injection, SH3YL1 knockout mice show lower levels of acute kidney injury biomarkers, decreased secretion of pro-inflammatory cytokines, decreased infiltration of macrophages, and reduced tubular damage compared with wild-type (WT) mice. The results strongly suggest that SH3YL1 is involved in renal failure in LPS-induced acute kidney injury (AKI) mice. We demonstrate that formation of a ternary complex of p22phox-SH3YL1-Nox4, leading to H2O2 generation, induces severe renal failure in the LPS-induced AKI model.